Kontribusi Pendidikan Agama Islam dalam Pembentukan Karakter dan Moralitas Peserta Didik: Studi Kepustakaan - Nelly (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2026)
Islamic Religious Education (IRE) plays a crucial role in shaping students’ moral character and strengthening their spiritual foundation in line with Islamic values. In the context of rapid social and technological change, character development has become an essential component of modern education. Therefore, Islamic education is expected to contribute significantly to fostering morally responsible individuals who maintain strong religious identity while adapting to contemporary challenges. This study employs a library research approach to examine the conceptual role of Islamic Religious Education in developing Islamic character among students. Relevant scholarly sources, including books and academic journal articles, were systematically analyzed to explore the processes, strategies, and challenges of character formation within Islamic education. The findings indicate that Islamic Religious Education contributes to character development through the internalization of moral values, the cultivation of positive habits, and the strengthening of spiritual awareness. The effectiveness of character formation is influenced by both internal and external factors, including family, school, and social environment. Strengthening collaboration among these elements is essential to ensure sustainable character development in educational settings.